Medical (Mal)Practice and the Illusion of Progress in Edward Berdoe’s St Bernard’s: The Romance of a Medical Student and Leonard Graham’s The Professor’s Wife: A Genealogical Analysis of Epistemological and Ethical Arguments in Two Late-Victorian Novels - Adrian Tait (Cahiers Victoriens et Edouardiens)
Literature affords important insights into the impact of medical discoveries, and this essay discusses two late-Victorian novels that focus on the epistemological and ethical problems generated by medicine’s scientization: Edward Berdoe’s St Bernard’s: The Romance of a Medical Student (1887), which focuses on a charitable hospital in which research is carried out on the poor, and Leonard Graham’s The Professor’s Wife: A Story (1881), which dramatizes the destructive, dehumanizing effects of science-driven practices, including vivisection, and their tragic consequences for the unsuspecting wife of a professor of physiology. Following Foucault’s genealogical approach, it is possible to trace the various ways in which these novels respond to the advent of a science-driven epistemology, which in turn generated a wholesale rejection of existing medical practices as unscientific and ineffectual, and a corresponding recognition that only intensive research might someday result in meaningful cures: until that time, medical practitioners could do little for their patients. This was the doctrine of medical or therapeutic nihilism. As these novels suggest, however, such a strictly rational interpretation of the healing art legitimated the exploitation of patients as experimental material, particularly those patients who were societally disempowered because poor or needy. This objectification of the patient body generated widespread opposition, as these novels testify. Moreover, new, science-driven ways of knowing were also linked to what British contemporaries regarded as the scandalous practice of vivisection, which in spite of legislation continued to preoccupy pioneers in the field of physiology. As these novels suggest, ethical issues were discounted by scientized medical professionals now intent on pursuing their research, often without care for the cost in suffering.